2012
DOI: 10.1111/j.1744-1633.2012.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of sentinel lymph node biopsy in patients with ductal carcinoma in situ and microinvasion

Abstract: Aim:  Ductal carcinoma in situ with microinvasion (DCISMI) is characterized by one or more areas of focal invasion, 1 mm or less in diameter. While pure ductal carcinoma in situ (DCIS) does not have the potential to metastasize to regional nodes, the presence of microinvasion makes lymph node metastasis possible, leading to current guidelines recommending staging of the axilla with sentinel lymph node biopsy (SLNB). However, there are few studies looking at the risk of lymphatic spread in patients with DCISMI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In patients with Mic, other studies have demonstrated that 0-10 % will have SLNs that contain metastatic deposits, with 2-7 % being macrometastatic disease. 1,6,7,[30][31][32][33][34][35] Although our 10 % incidence of a positive SLN for Mic was similar to previous studies, only 5.8 % of our Smic cohort had nodal disease. For macrometastatic nodal disease, our 1.9 and 3.3 % rates of involvement in Smic and Mic remained consistent with previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…In patients with Mic, other studies have demonstrated that 0-10 % will have SLNs that contain metastatic deposits, with 2-7 % being macrometastatic disease. 1,6,7,[30][31][32][33][34][35] Although our 10 % incidence of a positive SLN for Mic was similar to previous studies, only 5.8 % of our Smic cohort had nodal disease. For macrometastatic nodal disease, our 1.9 and 3.3 % rates of involvement in Smic and Mic remained consistent with previous studies.…”
Section: Discussionsupporting
confidence: 79%